ICARE AD‐US: Design of a prospective, single‐arm, multicenter, noninterventional real‐world study of aducanumab in the United States. (31st December 2021) - Galvin, James E.; Cummings, Jeffrey L.; Benea, Mihaela Levitchi; de Moor, Carl; Atri, Alireza; Porter, Verna R.; McEwen, Sarah C.; Rubino, Ivana
Abstract: Background: Aducanumab is a human monoclonal antibody that selectively targets aggregated forms of amyloid beta (Aβ), including soluble oligomers and insoluble fibrils, and, at the writing of this abstract, is currently under review by the US Food and Drug Administration (FDA), European Medicines Agency, and Pharmaceuticals and Medical Devices Agency (Japan). The efficacy and safety of aducanumab have been evaluated in 2 identically designed, randomized, placebo‐controlled, double‐blind Phase 3 studies in early Alzheimer's disease (AD); however, should aducanumab be approved, it will be critical to effectively evaluate its long‐term impact in the real world. Method: ICARE AD‐US is a prospective, single‐arm, multicenter, noninterventional study of aducanumab, as prescribed in a postmarketing, real‐world US setting. This Phase 4 observational study is designed to evaluate the safety and effectiveness of aducanumab in real‐world clinical practice per its FDA‐approved labeling in the US. The primary objective of the ICARE AD‐US study is to evaluate progression of AD in aducanumab‐treated patients as determined by a predefined, uniform set of cognitive, functional, and neuropsychiatric and global severity measures and to characterize the longitudinal impact of aducanumab on quality of life, disease burden, and health care resource utilization. ICARE AD‐US will also assess the long‐term safety of aducanumab as measured by the incidence of serious adverse events and the incidence of amyloid‐related imaging abnormalities‐edema (ARIA‐E). Biobanking of collected blood (plasma and serum) will provide the opportunity for future biomarker studies. Result: ICARE AD‐US aims to enroll approximately 6000 patients with AD over 4 years, including approximately 500 African American and 500 Hispanic/Latinx patients, from approximately 200 sites in the US. Patients will be monitored in a real‐world setting for a period of up to 5 years. Conclusion: The evidence generated in the ICARE AD‐US study will not only enable the collection of consistent long‐term efficacy and safety data to assess the impact of aducanumab treatment in the real world but will also support the measurement and characterization of AD progression and the optimization of clinical practice through standardization of the diagnosis of early AD and identification of individuals who may benefit from treatment.